Da finalidade protetiva do Direito Penal: a delimitação do inimigo penal como garantia de coexistência social - Nunes, Jéssica Ferreira (2018)
This dissertation aims at delimiting the politically identified criminal enemy in a legalistic state, starting from the study of the protective purpose of criminal law, which we developed by establishing a relationship between protected legal interest and criminal sanction, and its punitive justification. The constitutional parameters of the structuring of the power to punish are used to verify the possibility of unequal and repressive punishment in relation to the enemy, as well as observing the bases of justification of the function of the penalty. It should be emphasized that the criminal law of the enemy is a minor part of Günther Jakobs's systemic functionalist theory, so we only surround the limits of the controversy between communication and coercion, since the enemy was formulated from the penitent's conception of the doctrinaire German. This construction will be linked in part to the criminological analysis of the etiological paradigm to the social reaction to gauge the identification of the criminal; and, after the criminal policy of imbalance, between the Law and Order Movement and the Minimalism of the Guarantor. We also use the statistics of violence and punitive inflation to relate subjective fear to concrete and violent reality, which results the state of war from the enemy, in the face of the new (and old) criminal demands of modernity. In addition, we draw the panorama of the criminal enemy submerged in a functional right, which is identical as one who repeatedly practices serious crimes. We point out its philosophical precedents and its characteristics of "nonpersonal" and "phatic periculosity", in order to see its effects on the new expansionist culture, and the vestiges in the Brazilian legislation, before the transformations to the criminal dogmatic, even before the formalization of the conception of Jakobs. The aim is not to legitimize a theory of the enemy, but to rationalize a punitive justification by virtue of crimes of high gravity that violate the most important protected legal interest and attempt against peaceful coexistence.